Implementasi Enkripsi Data Secure Hash Algorithm (SHA-256) dan Message Digest Algorithm (MD5) pada Proses Pengamanan Kata Sandi Sistem Penjadwalan Karyawan - Sulastri, Santi; Putri, Riana Defi Mahadji (Jurnal Teknik Elektro, 2018)
There are various types of encryption that can be used, for example MD5 and SHA-256. However, usingÃ‚Â  MD5 or SHA-256 alone is not safe enough because it can be solved by using a brute force attack. The method of working is very simple is to try all possible combinations. This study aims to develop MD5 and SHA256 collaboration methods. Encryption is applied to the user's password on the web login system. Simulation results can be tested by measuring resistance to brute force attacks and the value of the avalanche effect (AE). From the results of the tests carried out by using attack software, the results of the application are quite safe from brute force attacks. From the AE test obtained the result with an AE value of 71% which means that the encoding result is good enough.